To solve the expression \( 3 \times -\frac{4}{5} - 10 \), we can follow these steps:
-
First, calculate \( 3 \times -\frac{4}{5} \): \[ 3 \times -\frac{4}{5} = -\frac{12}{5} \]
-
Now, we need to subtract 10 from \( -\frac{12}{5} \). To do this, we can convert 10 into a fraction with a denominator of 5: \[ 10 = \frac{50}{5} \]
-
Now we subtract: \[ -\frac{12}{5} - \frac{50}{5} = -\frac{12 + 50}{5} = -\frac{62}{5} \]
So, the final answer is: \[ -\frac{62}{5} \] or \(-12.4\) when converted to a decimal.